Antibacterial Action of Crude Solvent Extracts of Piper officinarum - Mrutyunjaya Rao, R.; Saranapu, Nareesh; Ramanujan, V.B.; Sastry, C.P.S.; Krishnaiah, Pendem; Srihari, Singampalli (Asian Journal of Chemistry, 2011)
Antimicrobial activities of various solvent extracts of Piper officinarum were determined against a wide variety of pathogenic bacteria. Crude extracts of Piper officinarum shows mild to moderate activities for most of the treated bacteria. Ethyl acetate extract, chloroform extracts and methanol extracts showed antibacterial effect against most of the tested organisms. It has been expected that the present work on antimicrobial screening of the plant materials will help researchers who wish to work in designing clinical drugs concerning the killer diseases.